2022
DOI: 10.1111/jan.15370
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of patient‐reported dignity and dignified care during acute hospital admission

Abstract: Aims: To synthesize quantitative evidence on levels of dignity during acute hospital admission and identify barriers and facilitators to patients' dignity or dignified care from the perspective of hospitalized patients. The secondary aim was to examine the relationship between dignity and demographic, clinical and psychological characteristics of patients.Design: A systematic review based on the protocol of the Preferred Reporting Items for Systematic reviews and Meta-Analyses guideline for reporting systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 96 publications
3
40
0
Order By: Relevance
“…The aim of the current systematic review was to identify PROMs used to measure patient dignity and/or dignified care during acute hospital admission, and to examine their methodological quality using the Consensus‐based Standards for the selection of health Measurement Instruments (COSMIN) methodology for systematic review of PROMs (Mokkink et al, 2018; Prinsen et al, 2018). The study was part of a larger project that synthesised quantitative evidence on levels of patients' dignity and/or dignified care during acute hospitalisation that has been published previously (Fuseini, Ley, et al, 2022).…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the current systematic review was to identify PROMs used to measure patient dignity and/or dignified care during acute hospital admission, and to examine their methodological quality using the Consensus‐based Standards for the selection of health Measurement Instruments (COSMIN) methodology for systematic review of PROMs (Mokkink et al, 2018; Prinsen et al, 2018). The study was part of a larger project that synthesised quantitative evidence on levels of patients' dignity and/or dignified care during acute hospitalisation that has been published previously (Fuseini, Ley, et al, 2022).…”
Section: Aimsmentioning
confidence: 99%
“…Hospitalised patients are at risk for loss of dignity in acute hospital settings that can be stressful and busy environments that limit opportunities for individualised and patient‐centred care (Calnan et al, 2013; Hirshon et al, 2013). Previous studies have reported moderate to severe loss of dignity (Liu et al, 2020; Wang et al, 2019) for patients in acute care settings, with loss of dignity associated with factors including hospitalisation (Chochinov, Hack, Hassard, et al, 2002; Fuseini, Ley, et al, 2022), type of hospital ward (Karimi et al, 2019), patients' functional status (Monforte‐Royo et al, 2018) and demographic variables (Karimi et al, 2019; Salehi et al, 2020). Bláhová et al (2020) posited that care in acute hospital settings is often routinised with a tacit neglect to person‐centred care.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review on patient‐reported dignity during acute hospitalization demonstrates few quantitative studies on hospitalized older adults' dignity and paucity of suitable validated dignity‐related PROMs for hospitalized older adults (Fuseini, Ley, et al, 2022), particularly for the Ghanian population. The few existing dignity‐related PROMs were developed and validated for patients in long‐term care (Dong et al, 2021; Oosterveld‐Vlug et al, 2014; Ostaszkiewicz et al, 2020), end‐of‐life care (Chochinov et al, 2008; Periyakoil et al, 2009; Vlug et al, 2011) or for community‐dwelling older adults (Jacelon & Choi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, human dignity is unique to each person and is shaped by their relationships with others. Additionally, there is a sense that human dignity is a comprehensive concept that extends beyond the sum of its components 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a sense that human dignity is a comprehensive concept that extends beyond the sum of its components. [11][12][13] Maintaining patient dignity is a fundamental part of providing quality care. 14 Patients recognize dignity as one of the most important aspects of care and make a direct connection between their sense of dignity and respect and the overall quality of their care.…”
mentioning
confidence: 99%